The non-target effects of the introduced parasitoid Trigonospila brevifacies (Hardy) (Diptera: Tachninidae) on the native fauna of New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Palmerston North, New Zealand - Munro, Vanessa M W (Massey University, 1999)
The Australian tachinid parasitoid Trigonospila brevifacies (Hardy) (Diptera: Tachinidae) was introduced to New Zealand 30 years ago as a biological control for the exotic orchard pest Epiphyas postvittana Walker (Lepidoptera: Tortricidae). Trigonospila brevifacies, an endoparasitoid of late-instar lepidopteran larvae, was introduced concurrently with Xanthopimpla rhopaloceros Krieger (Hymenoptera: Ichneumonidae), a parasitoid of lepidopteran pupae. Trigonospila brevifacies is now known to attack several non-target pest and non-pest lepidopteran species. The impact of T brevifacies on non-target fauna was investigated. Life history data (i.e., longevity, fecundity, productivity and sex ratio) for T. brevifacies were quantified in the laboratory. These data and field data were used to investigate whether superparasitism is an adaptive reproductive strategy for this species by comparing the return in adult progeny per egg for single and multiple egg clutches. Superparasitism may be advantageous for the survival of rare non-target hosts. Data from a two-year, six-site survey of native forests determined that T. brevifacies attacked eight non-target Lepidoptera. The characteristic common to the phylogenetically diverse host group was that all are concealed feeders. Laboratory testing showed that pre-imaginal conditioning of parasitoid larvae did not confer adults with a preference for the host species in which they were reared. Quantitative food web data from a two-year field survey showed that T. brevifacies was the numerically dominant parasitoid of the species attacking native Tortricidae at sub-canopy levels and that it competed for hosts with 12 native and one other introduced species of parasitoid. The abundance of larval hosts and T brevifacies was compared between the edges and centres of forest patches. Host density was determined by quadrat counts and parasitoid abundance by sticky traps. Both larval hosts and the parasitoid were more abundant at the forest edge. Trap hosts were also used to quantify parasitism levels along edge to forest-centre tansects. Parasitism by T. brevifacies was highest at forest edges declining to almost zero at 30m into a forest, indicating that forest centres with continuous canopy should offer hosts' refuge from T. brevifacies parasitism. Archival and field data were used to determine the present geographical ranges of T. brevifacies and X. rhopaloceros and climatic data were used to predict where else in New Zealand these two parasitoids are likely to colonise in the future.
Thesis includes chapter (author's manuscript) published as: Munro, V. M. W. (1998). A Retrospective Analysis of the Establishment and Dispersal of the Introduced Australian Parasitoids Xanthopimpla rhopaloceros (Krieger) (Hymenoptera: Ichneumonidae) and Trigonospila brevifacies (Hardy) (Diptera: Tachinidae) within New Zealand. Biocontrol Science and Technology, 8:4, 559-571. To link to this article: http://dx.doi.org/10.1080/09583159830072
Keywords: Host-parasite relationships; Insects; Parasites; Parasitic insects; Trigonospila brevifacies; Diptera: Tachninidae; Agricultural pests; Biological control; New Zealand